A comprehensive review on the role of dopamine in the pathophysiology of tardive dyskinesia - Kandasamy, Krishnaveni; Paramanandham, Abinaya; Suthi Kumari, Goshika Russel; Ramalingam, Kameswaran (International Journal of Research in Medical Sciences, 2023)
Tardive dyskinesia (TD) is a neurological syndrome characterized by involuntary, repetitive, and unusual movements that primarily impact the orofacial region while also extending to other body parts, encompassing chorea, dystonia, tics, buccolingual stereotypy, and akathisia. This condition stems from iatrogenic factors, particularly the chronic administration of medications that obstruct dopamine receptors. Predominantly implicated are antipsychotic drugs, utilized primarily for schizophrenia and bipolar disorder treatment. These drugs modulate dopamine levels, yet prolonged usage can induce alterations in dopamine receptor sensitivity and disruptions in dopaminergic pathways, consequently fostering TD. Dopamine, a pivotal neurotransmitter governing motor control, motivation, reward processing, and emotional regulation, exerts its effects through distinct dopamine receptor types, of which the D2 subtype assumes particular significance in TD development. The persistent blockade of D2 receptors by antipsychotics prompts a compensatory surge in receptor numbers and sensitivity, ultimately contributing to TD's emergence. In essence, TD reflects a complex interplay between medical intervention and neurological intricacies. The protracted influence of antipsychotics on dopamine receptors highlights the delicate equilibrium essential for optimal brain function. The unconventional movements characterizing TD underscore the intricate role of dopamine and its receptors in orchestrating neural equilibrium.